The Divergent Dimerization Behavior of N‐Substituted Dicyanomethyl Radicals: Dynamically Stabilized versus Stable Radicals. Issue 52 (28th November 2017) - Okino, Kohei; Hira, Shota; Inoue, Yuki; Sakamaki, Daisuke; Seki, Shu
Abstract: Herein, we demonstrate that the dimerization behavior of amine‐substituted dicyanomethyl radicals can be switched from σ‐ to π‐dimerization simply by varying the electron‐donating substituents. For dicyanomethyl radicals with a 4, 4′‐ditolylamine (DT . ) or a phenothiazine (PT . ) substituent, the monomeric radical form and the corresponding dimer connected by a reversible C−C bond (σ‐dimer) are in equilibrium in solution. On the other hand, the radical with the julolidine skeleton (JD . ) does not undergo σ‐dimerization and was isolated as a stable radical in spite of the absence of bulky protecting groups. X‐ray single‐crystal analysis revealed thatJD . forms the π‐dimer in the crystalline state, and variable‐temperature spectroscopy showed thatJD . is in equilibrium with the π‐dimer in toluene solution. DFT calculations point to the importance of electrostatic interactions as a driving force for the π‐dimerization ofJD . because of its polarized structure. Abstract : Unchained : Amine‐substituted dicyanomethyl radicals have been known to form σ‐dimers. However, a dicyanomethyl radical with the julolidine skeleton (JD . ) does not form the σ‐dimer and was successfully isolated as a stable radical in spite of the absence of bulky protecting groups. This radical is in equilibrium with its π‐dimer in toluene solution.